PWE-050 A protocol to avoid corticosteroid exposure prior to crohn's disease requiring luminal surgery. (22nd June 2015) - Patel, KV; Johnston, EL; Fong, SC; Nasr, I; Amadi, C; Westcott, E; Williams, A; Darakhshan, A; Dunn, JM; Anderson, S; Irving, PM; Sanderson, JD
Abstract : Introduction: Corticosteroids (CS) are prescribed to control inflammatory and obstructive symptoms in Crohn's disease (CD). Preoperative CS are associated with higher risk of all complications post-operatively including sepsis, anastomotic breakdown and venous thromboembolic disease.High doses of CS also preclude a primary anastomosis. In our institution, we have implemented a protocol to prevent CS administration or permit a rapid wean in patients requiring ileal/ileocaecal resection, maximising the use of exclusive enteral nutrition (EEN) or parenteral nutrition (PN). This study aimed to determine the achievability of CS avoidance in this setting. Method: In patients selected for ileal/ileocaecal resection, EEN (with either Modulen IBD Nestle or Fortisip Nutricia, as tolerated) was prescribed to a target dose of 30 kcal/kg. Acute sepsis was controlled with intravenous and/or oral antibiotics. If EEN was not tolerated because of obstructive symptoms, PN was instituted or surgery expedited. Patients were not offered this protocol if they had minimal symptoms, adequate nutritional status and no CS exposure. Results: In total, 39 patients with CD had IC resection over a period of 20 months from January 2013. 9 of these underwent urgent surgery due to symptom severity (severe obstruction or suspected cancer where delay not possible [4 of 9 on CS (45%)]. 8 patients with stable symptoms secondary to fibrotic stricture (4 on biologic, 4 on immunomodulator), adequate nutritional status and CS free were not suitable for the protocol. 22 patients with acute symptoms were therefore included. All had penetrating and/or stricturing disease. 8 patients were receiving CS of whom 7 (88%) successfully weaned off CS for greater than 4 weeks using EEN. 1 did not tolerate EEN and proceeded to surgery on CS. A further 11 of 22 patients successfully treated via protocol to avoid CS (EEN n = 7, PN n = 4) 3 patients did not tolerate/declined EEN/PN and proceeded to expedited surgery. Hence, in all patients suitable for the protocol, CS were successfully avoided (14/14 patients, 100%) and wean >4 weeks successful in majority (7/8 patients, 87.5%). CS exposure was successfully avoided in 21 patients via protocol (95.5%). Conclusion: Aggressive use of EEN or PN provides an effective approach to avoid CS exposure, optimise nutrition and control acute symptoms in patients selected for IC resection. The implementation of the protocol requires close liaison between gastroenterologists, colorectal surgeons and dieticians. The protocol does not delay emergency surgery. Disclosure of interest: None Declared.